Community Perspectives on the Impact of Climate Change on Health in Nunavut, Canada - Healey, G.K.; Magner, K.M.; Ritter, R.; Kamookak, R.; Aningmiuq, A.; Issaluk, B.; Mackenzie, K.; Allardyce, L.; Stockdale, A.; Moffit, P. (ARCTIC, 2011)
The purpose of this study was to explore community perspectives on the most important ways that climate change is affecting the health of northern peoples. The study was conducted in Iqaluit, Nunavut, using a participatory action approach and the photovoice research method. Participants identified themes and patterns in the data and developed a visual model of the relationships between the themes identified. Five themes emerged from the data: the direct impacts of climate change on the health of individuals and communities, the transition from past climates to future climates, necessary adaptation to the changing climate in the North, the call to action (individual, regional, and national), and reflection on the past and changing knowledge systems. A climate change and health model was developed to illustrate the relationships between the themes. Participants in this study conceptualized health and climate change broadly. Participants believed that by engaging in a process of ongoing reflection, and by continually incorporating new knowledge and experiences into traditional knowledge systems, communities may be better able to adapt and cope with the challenges to health posed by climate change. L’objectif de cette étude consistait à explorer diverses perspectives communautaires quant aux manières les plus importantes dont le changement climatique a des incidences sur la santé des gens du Nord. L’étude a été réalisée à Iqaluit, au Nunavut, au moyen d’une méthode d’action et de recherche participative faisant appel à la « photovoice ». Les participants ont déterminé les thèmes de même que les tendances caractérisant les données, puis ont abouti à un modèle visuel pour établir des relations entre les thèmes ainsi déterminés. Les données ont donné lieu à la formulation de cinq thèmes, soit les incidences directes du changement climatique sur la santé des gens et des collectivités; la transition des anciens climats aux nouveaux climats; l’adaptation nécessaire au climat changeant dans le Nord; un appel à l’action ...